The mediating role of effective working capital management on the growth prospects of Small and Medium Enterprises in Polokwane Municipality - Masocha, R.; Dzomonda, O. (SAAPAM (South African Association of Public Administration and Management), 2016)
The paper assesses the mediating role of effective working capital management on the growth prospects of small and medium enterprises (SMEs) in Polokwane Municipality. SMEs form the backbone of the economies of most countries in the world. Hence growing the number of SMEs in the economy and growing the size of existing ones can go a long way towards achieving South Africa's developmental needs. Furthermore, improving the growth and sustainability of an SME sector is a remarkable milestone towards solving South Africa's developmental challenges such as unemployment, poverty and income inequality. The SME sector is an active and vibrant force for economic growth, innovation and job creation for both developed and developing countries. There is consensus among economists and policy makers on the importance of the SME sector as an engine for economic growth. However, SMEs in South Africa continue to fail. This random failure rate casts doubt on this sector's ability to be a sustainable solution to developmental challenges facing South Africa. This contribution is of the argument that a well designed and implemented working capital management can be a panacea to high failure rate of SMEs in South Africa. This study used a quantitative research methodology with a descriptive research design. 50 SME owner/ managers participated in the survey and data was collected through a self-administered questionnaire. Data analysis included descriptive statistics, Pearson Correlation coefficient and the Canonical Correlation Analysis. The Cronbach's alpha was used to measure reliability of the data collection instrument. The results indicated that SMEs are not effectively managing their working capital. The paper concludes by emphasizing the need for SMEs to effectively manage their working capital as it is the lifeblood of all growing businesses.
Article
Keywords: Working capital management; Developmental challenges; Growth; SMEs; Sustainability; Small businesses; Working capital; Sustainable development; Economic development